Asesmen Nasional: Tolok Ukur Kualitas Pendidikan Indonesia ? - Desya Nathasya Ramadiana; Masduki Asbari; Risha Putri Laksana (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to measure the quality of education in schools. In this study report, a qualitative descriptive method was used by observing closely because the data source was obtained by listening to the oral narrative from the Indonesian Ministry of Education and Culture's YouTube channel entitled "Siniar #PojokDikbud: Measuring the quality of education in schools with national assessments" presented by resource person Anindito Aditomo. Study results This explains that national assessment is an important tool in measuring the quality of education in schools. This article discusses the meaning of national assessment, its objectives, and why it is a key factor in understanding the quality of education.